KOMUNIKASI ANTAR PRIBADI PADA ORANG TUA LANJUT USIA DI PANTI RUMAH DOA KANAAN - Missah, Christy Lidya (ACTA DIURNA KOMUNIKASI, 2014)
By looking at the complexity of the problems faced by the elderly, ranging from physical condition to writers interested in the psychological aspects of common communication activities conducted elderly. If related to the things that hinder the elderly parent communication, language skills are good and true, when communicating with fellow elderly, in contrast to the facts in the field. It should be examined how interpersonal communication in the elderly because communication is a tool to establish the relationship between people and the disruption of communication which distorts the message in the elderly. Meaning of language symbols in the elderly, varies according to the character of the elderly. Authors interested in knowing whether the meaning of the symbols of language in interpersonal communication elderly nursing dipanti this, because when communicating elderly feel more familiar, with such sadness and burden their minds can be reduced (DeVito, 1997: 28). Based on the above data and issue the writer is interested to examine the interpersonal communication with the elderly parents as well as fellow seniors in a nursing home caregivers House of Prayer Canaan Village. In interpersonal communication Elderly Parents in Nursing Home Elderly Canaan prayer "with the focus of research and the following results interpersonal communication events that occurred in the elderly in a nursing home prayer house Kanaan.Aktivitas interpersonal communication on the elderly in this place that through their interactions in the activities of worship, prayer groups, and group sharing time. Communication activities are operating effectively in accordance with the handling in building relationships and maintaining relationships among the elderly who have a close relationship. Things that hinder interpersonal communication on the elderly in this place there are a few things related to physical factors, psychological, mental and spiritual. The first obstacle is influenced by physical factors that obstacle with the term cut corners, this happens because the communicator and communicant misinterpret the meaning of the language of communication dimaksudkan.Hambatan both the quality of elderly people who have impaired hearing, it is still influenced by physical factors of elderly which has not allowed the effectiveness of communication. The third obstacle is the difference factor field of experiences and frames of experiences in the elderly. Last communication barriers that are found in the elderly that is the aggressive nature of the communication. Meaning of language symbols in the elderly in a nursing home House of Prayer Kanaan.Bentuk interpersonal communication in the elderly with other elderly fellow influenced by the meaning of language symbols. Through the signaling of a symbol, then the elderly can express feelings, thoughts, intentions, by reading the symbols displayed by others. Essentially meaning of symbols in the language of interpersonal communication When elderly parents takes place, they have the same meaning of the symbols of language, which means they themselves would like to note, in terms of sharing what they are thinking or feeling. Meanwhile, when communicating with non-elderly interpersonal, language symbols meanings they convey that they want to be appreciated, respected and given the responsibility for its existence, particularly addressed to his family own. Abstrak Dengan melihat begitu kompleksnya permasalahan yang dihadapi orang tua lanjut usia, mulai dari kondisi fisiknya hingga segi psikologis penulis tertarik dengan aktivitas komunikasi yang lazim dilakukan lansia. Jika dikaitkan dengan hal-hal yang menghambat dalam komunikasi orang tua lanjut usia, kemampuan berbahasa yang baik dan benar, ketika berkomunikasi dengan sesama lansia, berbeda pada fakta dilapangan. Perlu ditelitinya bagaimana komunikasi antar pribadi pada orang tua lanjut usia sebab komunikasi merupakan alat untuk menjalin hubungan antarsesama dan adanya gangguan dalam komunikasi yang mendistorsi pesan pada lansia. Pemaknaan simbol bahasa pada lansia, berbeda-beda sesuai dengan karakter lansia. Penulis tertarik mengetahui apakah makna simbol bahasa pada komunikasi antar pribadi lansia dipanti werda ini, karena ketika berkomunikasi lansia merasa lebih akrab, dengan demikian kesedihan dan beban pikiran mereka bisa berkurang.(Devito,1997:28).Berdasarkan data dan masalah diatas penulis tertarik untuk meneliti komunikasi antar pribadi orang tua lanjut usia dengan sesama lansia dan juga pengasuh di Panti Werda Rumah Doa Kelurahan Kanaan. Komunikasi AntarPribadi Pada Orang Tua Lanjut Usia di Panti Werdha Rumah doa Kanaanâ€ dengan fokus penelitian dan hasil penelitian sebagai berikut Aktivitas komunikasi antarpribadi yang berlansung orang tua lanjut usia di Panti Werda Rumah doa Kanaan.Aktivitas komunikasi antar pribadi pada orang tua lanjut usia ditempat ini yaitu lewat interaksi mereka dalam kegiatan ibadah, kelompok doa, dan waktu sharing kelompok. Aktifitas komunikasi berjalan dengan efektif sesuai dengan penanganan dalam membangun hubungan dan mempertahankan hubungan antar sesama lansia yang memiliki hubungan dekat. Hal-hal yang menghambat komunikasi antarpribadi pada orang tua lanjut usia ditempat ini ada beberapa hal yang terkait dengan faktor fisik, psikis, mental dan spiritualnya. Hambatan yang pertama yang dipengaruhi oleh faktor fisik yaitu hambatan dengan istilah potong kompas, hal ini terjadi karena si komunikator dan si komunikan salah mengartikan makna bahasa yang dimaksudkan.Hambatan komunikasi yang kedua yaitu kualitas pendengaran lansia yang sudah terganggu, hal ini masih dipengaruhi faktor fisik lansia yang sudah tidak memungkinkan terjadinya efektivitas komunikasi. Hambatan yang ketiga yaitu adanya perbedaan faktor field of experiences dan frame of experiences pada orang tua lanjut usia. Hambatan komunikasi yang terakhir ditemukan pada orang tua lanjut usia yaitu adanya sifat agresif dalam berkomunikasi. Makna simbol bahasa pada orang tua lanjut usia di Panti Werda Rumah Doa Kanaan.Bentuk komunikasi antarpribadi pada orang tua lanjut usia dengan sesama lansia lainnya dipengaruhi oleh pemaknaan simbol bahasa. Melalui pemberian isyarat berupa simbol, maka kaum lansia dapat mengutarakan perasaan, pikiran, maksud, dengan cara membaca simbol yang ditampilkan oleh orang lain. Intinya pemaknaan simbol bahasa Ketika komunikasi antarpribadi pada orang tua lanjut usia berlangsung, mereka memilki makna simbol bahasa yang sama, yaitu bermakna diri mereka ingin diperhatikan, dalam hal berbagi apa yang sedang mereka pikirkan atau rasakan. Sedangkan ketika berkomunikasi interpersonal dengan yang bukan lansia, makna simbol bahasa yang mereka sampaikan yaitu mereka ingin dihargai, dihormati dan diberikan tanggung jawab atas keberadaannya, khususnya ditujukan kepada keluargannya sendiri.